Exploring Emotions in Inside Out: Semiotic Perspective on Language - Naufal Nafis; Suhartawan Budianto; Kusuma Wijaya (Gudang Jurnal Multidisiplin Ilmu, 2025)
This study examines how emotions are expressed through language in Inside Out (2015) using Saussure’s semiotic theory. The research focuses on how dialogues spoken by Joy, Sadness, Fear, Disgust, and Anger function as signs that represent Riley’s emotional states. Using a qualitative descriptive method, the study analyzes the relationship between signifier (words and phrases used in dialogue) and signified (the intended emotional meaning). The findings indicate that emotions in the film are conveyed through specific verbal expressions, showing how language operates as a system of signs. This research contributes to the field of semiotics by providing insights into how words shape emotional meaning in animated storytelling.